Synthesis and Characterization of Various Xanthates and Their Effects on Germination and Early Seedling Growth in Wheat (Triticum aestivum L.) - Rani, Alka; Gupta, C.S. (Asian Journal of Chemistry, 2013)
Potassium n-propyl xanthate potassium iso-propyl xanthate, potassium n-butyl xanthate and potassium iso-butyl xanthate were synthesized and characterized by melting point, elemental analysis and infrared spectra and their effect on germination and early seedling growth in wheat (Triticum aestivum L.) were studied. All chemical treatments decreased per cent germination length and dry weight of shoots decreased at all concentrations except at 5 and 10 ppm n-propyl xanthate. Root length also decreased except at 5,10 and 25 ppm of potassium iso-propyl xanthate and potassium iso-butyl xanthate, root dry weight decreased with all chemical treatments except at 5 and 10 ppm in case of potassium n-butyl xanthate.